Assessing the Accuracy of Casting and Additive Manufacturing Techniques for Fabrication of a Complete Palatal Coverage Metal Framework. Issue 7 (11th June 2019) - Forrester, Keaton; Sheridan, Ryan; Phoenix, Rodney D.
Abstract: Purpose: To provide information regarding the accuracy of additive manufacturing in comparison to conventional casting, specifically for fabrication of complete palatal coverage metal frameworks. Materials and Methods: Three additive manufacturing techniques were tested: selective laser melting (SLM), electron beam melting (EBM), and computer‐aided design/cast (CADcast), with conventional casting as the control. Both the SLM and EBM groups were tested pre‐ and post‐finishing, for a total of six test groups (n = 10/group). A digital master design was used as the standard to which all frameworks were digitally compared by best‐fit analysis, which generated root mean square values using proprietary software. A one‐way ANOVA was conducted to test for statistical differences among materials, followed by a post‐hoc multiple comparison test (Tukey's test HSD). Surface roughness for one framework arbitrarily selected from each group was analyzed using a profilometer. Results: There was a significant difference in accuracy among the materials ( F = 99.79,   p  < 0.0001). A post‐hoc Tukey test indicated that CADcast differed significantly from the other five materials (i.e., most accurate, p < 0.01). EBM prefinished and EBM finished were both significantly different from the other materials (i.e., least accurate). Color mapping images help visualize the differences between each framework compared to the master design. The surface roughness values ranged from 22 to 63.5 µm, with CADcast being the smoothest, and EBM prefinished the roughest. Conclusions: CADcast and SLM techniques were as or more accurate than the conventional technique for producing an uncomplicated framework design. Further investigation is recommended regarding the surface roughness of additive manufacturing products and potential biological complications.